1985
DOI: 10.1185/03007998509109606
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of econazole (‘Gyno-Pevaryl’ 150) in vaginal candidosis during pregnancy

Abstract: An open, multi-centre study was carried out in 117 pregnant women presenting with vaginal candidosis to assess the effectiveness of econazole in providing mycological control and symptom relief, and in preventing, as far as possible, the risk of contamination of the newborn: nearly 50% of the patients were in the last month of pregnancy. Patients received a single course of econazole given as 1 vaginal pessary (150 mg) on 3 consecutive days. Clinical and mycological assessments were made 1 week after the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In another study, 117 pregnant women with a mean gestation age of 30 weeks were treated with a 3‐day regimen of vaginal econazole. Authors reported no congenital anomalies, although three stillbirths and one in utero death were reported . In 2002, Kragie et al .…”
Section: Antifungalmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 117 pregnant women with a mean gestation age of 30 weeks were treated with a 3‐day regimen of vaginal econazole. Authors reported no congenital anomalies, although three stillbirths and one in utero death were reported . In 2002, Kragie et al .…”
Section: Antifungalmentioning
confidence: 99%
“…Authors reported no congenital anomalies, although three stillbirths and one in utero death were reported. 53 In 2002, Kragie et al 54 studied azole antifungals for their potential to inhibit aromatase enzyme and contribute to adverse events in human and animal pregnancies. They reported the most potent inhibitor to be econazole, and the least potent to be miconazole.…”
Section: Clotrimazole (Category B)mentioning
confidence: 99%